Systematic application and removal of protective equipment in the assessment of multiple topographies of self-injury. - Moore, James W (2004)
We evaluated the effects of systematic application and removal of protective equipment on three topographies of self-injurious behavior (SIB) exhibited by a girl who had been diagnosed with autism. Results showed that when protective equipment was applied, SIB decreased to near-zero levels. In addition, withdrawal of protective equipment for specific topographies of SIB (by removing only the corresponding padding) increased rates of SIB only for that topography of SIB. Next, a functional analysis of hand SIB showed that protective equipment suppressed this behavior in all conditions and that the behavior was maintained by automatic reinforcement when padding was removed. Results are discussed in terms of sensory extinction as a possible mechanism responsible for response suppression.